Der Todesking - Kopp, Hermann 1954-; Lorenz, Daktari Bernd 1962-; Walton, John Boy ca. 20. Jh (Arrow Films, 2018)
"The second feature film from German provocateur Jörg Buttgereit [...] presents seven suicides across seven days of the week. As a chain letter from the self-proclaimed Brotherhood of the 7th Day circulates encouraging its recipients to end their lives, a series of grim murder-suicides unfold. In one vignette, a young woman massacres a room of concert-goers before turning the gun on herself; in another, a man, driven to madness by some unspecified mental disturbance, repeatedly slams his head into a wall before collapsing in a pool of his own blood. [...]." Regarded by many as director Jörg Buttgereit s most accomplished work, "Der Todesking" is an existential masterpiece - a powerfully haunting howl of rage from one of the genre s most underrated filmmakers." [amazon.co.uk]
Original: Bundesrepublik Deutschland 1990
Bildformat 1.33:1
3-Disc director-approved limited edition content: director's approved HD transfer from the original 16mm negative ; HD Blu-ray (1080p) and SD DVD presentations ; original stereo audio (uncompressed PCM on the Blu-ray) ; optional English subtitles ; limited edition packaging featuring new artwork by Gilles Vranckx ; limited edition certificate featuring original artwork ; Replica Brotherhood of the 7th Day Chain Letter ; "Der Todesking" Soundtrack CD ; limited Edition 60-page book
[Extras] Blu-ray & DVD "Der Todesking: audio commentary by Jörg Buttgereit and co-writer Franz Rodenkirchen ; "From Bundy to Lautréamont" - Jörg Buttgereit in conversation with journalist Graham Rae at the 2016 Manchester Festival of Fantastic Films ; Todesmusik composer Hermann Kopp on his numerous collaborations with Jörg Buttgereit ; Skeleton Under the Skin journalist and Buttgereit fan Graham Rae on Todesking tattoo culture ; The Making of "Der Todesking" - vintage production featurette; footage from the original 1990 Berlin premiere ; Corpse Fucking Art - 1992 documentary bringing together the making of featurettes of "Nekromantik", "Der Todesking" and "Nekromantik 2" ; "Der Gollob" (1983, 25 mins) - short film by Jörg Buttgereit, newly transferred in HD and viewable with optional director s audio commentary ; two short films by producer Manfred O. Jelinski: "Die Reise ins Licht" (1972, 27 mins) and "Geliebter Wahnsinn" (1973, 7 mins) ; still gallery ; Jörg Buttgereit trailer gallery
Keywords: Film; DVD-Video; Blu-Ray-Disc; CD